Ingestão dietética e índice inflamatório dietético associado ao estadiamento tumoral em pacientes com neoplasia da tireoide no estado do Rio Grande do Norte - Neri, Julianna Lys de Sousa Alves (2021)
Thyroid cancer (TC) is the most common tumor of the endocrine system. Dietary factors may have benefits in decreasing the risk of TC or its severity. The study aimed to evaluate the association between food and dietary intake, inflammatory and dietary index and histopathological tumor staging (angiolymphatic invasion, thyroid extension, lymph node metastasis and multicentricity) of patients with thyroid cancer in the state of Rio Grande do Norte. This is a cross-sectional study that included 98 individuals assisted by the League Against Cancer, who underwent total or partial thyroidectomy for suspected malignant thyroid neoplasm. To assess food and dietary intake and the Dietary Inflammatory Index (DII), the 24-hour recall (24hR) collected in three moments was applied. The analysis and cytological and histopathological classifications of the tumors were performed at the Pathology Laboratory of Hospital Luiz Antônio (HLA) by pathologists. Student's t, Mann–Whitney, Chi-square or Fisher's exact test and Binary Logistic Regression tests were used when appropriate. Patients were classified as: benign (n=25) and malignant (n=73) neoplasms. Significant associations were found between Cholesterol (p=0.007), Iodine (p=0.028), Omega 3 (p=0.031), Vitamin D (p=0.041) and the presence of malignant nodules, with Cholesterol intake > 246, 97 g associated with 13.00 times greater chances of malignancy. Vitamin D (p=0.031) and Omega 3 (p=0.039) were associated with the presence of angiolymphatic invasion. Calcium (p=0.008) and Caffeine (p=0.027) were associated with extrathyroidal extension, with calcium intake > 640.06 mg representing a protection factor of 5.43. Vitamin E was associated with the presence of lymph node metastasis (p=0.029). Vitamin B6 (p=0.026) was associated with the presence of multicentricity. Vitamin A intake >276.17 mcg was associated with 4.714 and 6.111 greater odds of presence of multicentricity and extrathyroidal extension, and riboflavin intake >2.4 mg was associated with 4.375 greater odds of presence of extrathyroidal extension. Regarding the IID, no associations were found with the histopathological staging of CT. Eating habits seem to be associated with the histopathological tumor staging of thyroid carcinoma, requiring further studies and investigations that, if confirmed, may have important implications for public health.